Design of Service Information System at the Social Service of West Sulawesi Province - Karmila; Zulhajji (International Journal of Information Systems and Technology, 2025)
This research was developed to facilitate data processing and information dissemination. This study aims to determine the results of the design of a web-based service information system at the West Sulawesi provincial social service based on ISO 25010 quality standards. This study uses a prototype development model. The data collection technique uses interview techniques, questionnaires and documentation. The system testing uses ISO 25010 which focuses on testing functional suitability, reliability, portability and usability. The results of the system testing using the ISO 2010 standard are in the functional suitability test tested by system experts by filling out a questionnaire containing 114 questions related to the functions designed in the developed system, the functional suitability test value is in the good category; in the reliability test using the help of webserver stress tool 8 which consists of three types of tests, namely click test, time test and ramp test and it is stated that the information system developed has met the reliability aspect; in the portability test of the West Sulawesi provincial social service information system, it was carried out using broweserstack.com and it was stated that the information system developed has a high portability aspect; In the usability test, a questionnaire containing 25 questions was used with 30 respondents and the responses obtained from respondents were that the information system developed was in the very feasible category.